Scientific and Professional Degrees in Russia: Developing Traditions into the Future - A. I. Rudskoy; A. I. Borovkov; P. I. Romanov; N. S. Grishina (Высшее образование в России)
When studying the history of Russian education, one becomes convinced of the validity of the dialectical principles of spiral development. The period of cyclicality in the history of attestation of scientific personnel is approximately equal to a century. In the first quarter of every century, starting from the time of the tsar Peter the Great, events took place that brought the system to a fundamentally new level. But at the same time, the fundamental foundations laid by the tsar Peter the Great and Lomonosov remain constant. Analyzing the attestation system development spiral, we find ways to solve urgent problems, and the foremost among them is ensuring Russia’s technological sovereignty. A similar problem stood a century ago. It was fully resolved in the USSR, but the foundations for its solution were laid in 1917 in the decree issued by the Russian Provisional Government: “On granting the Petrograd Polytechnic Institute the right to award academic degrees”. In the socioeconomic conditions of the modern Russia, we need new solutions. In this article we offer them